Cultural Inbetweenness and the Dilemma of Identity in Margaret Atwood’s The Blind Assassin (2000) - Zidelkheir, Hanin; Kharchi, Meriem; Mouissa, Fattoum (University of Ammar Theledji -Laghouat, 2022)
Identity construction has always been a question of interest in postmodern writings. Postmodern literature conceptualizes the issue of identity through different social settings. Margaret Atwood is one of the main authors who depict the process of identity development and crisis. Predominantly, she portrays in her writings the crucial journey of identity formation. Also, she pictures the main reasons behind the construction of troubled self / identity, chiefly, in her work The Blind Assassin. This novel portrays the struggle of different characters in Canada during the 1930’s and 1940’s. Atwood uses the shift between past and present to highlight the different processes of constructing an identity. This dissertation discusses the issue of identity through different approaches such as the psychological approach, adding to the humanistic approach to better interpret the different mind settings and identities of the main characters in the selected novel. Accordingly, this work divulges the characters’ struggle with identity construction. This paper comes at the result that social, political, and economic aspects might affect the psyche of characters, leading to predicaments at the level of identity